การพัฒนาปัจจัยแห่งความสำเร็จและการจัดการความเสี่ยงองค์กรเพื่อสร้างการเจริญเติบโตของธุรกิจท่องเที่ยวฝั่งอันดามันของประเทศไทย - วิภาดา เถาธรรมพิทักษ์ (มหาวิทยาลัยสงขลานครินทร์, 2023)
In the present, operating tourism business have been facing several challenges including rapidly changed in social, technologies, tourist behaviors, tourism trends, as well as various situations that may affect the business. This study aimed to develop the key success factors and risk management for operating tourism business in order to enhance the business growth of the tourism businesses along the Andaman Coast of Thailand. Mixed research methodology between quantitative and qualitative researches was employed in this study. Data was collected from four-hundred and nineteen tourism entrepreneurs along the Andaman Coast of Thailand using a questionnaire and thirty tourism entrepreneurs using an interview. In addition, mixed sampling method between quota and purposive approaches was used in this study. Descriptive and Inferential Statistics were used to analyze in the context of quantitative research and content analysis was used for qualitative research. The research results from statistical analysis revealed a high level of key success factor adoption in operating tourism business included hygiene standard, service quality, and business partner. Whereas, the level of risk management adoption in operating tourism business, in overall, was in a moderate level. Moreover, the overall business growth of the tourism entrepreneurs has been declined due to the COVID-19 pandemic situation. Results from ordinary least square regression (OLS) revealed the positive influences of the key success factors and risk management on the business growth. In addition, implementing risk management in operating tourism business played roles and had influenced as the mediator between the key success factors and the business growth, and a role of the business location between the first and second tiers that had influenced as the moderator as well. In terms of recommendations, implementing the key success factors and risk management in operating tourism business appropriately and accordingly with the context of business will evidently influence the business growth in a better direction.